Cognitive bridge between geometric and numerical learning in monkeys - Jessica F. Cantlon; Logan R. Brownell; Jialin Li; Caroline M. DeLong (Proceedings of the National Academy of Sciences, 2025)
Educational research highlights strong developmental links between numerical and spatial cognition in humans, often shaped by cultural tools like the number line. However, emerging evidence suggests that these number–space connections may reflect our evolutionary history and emerge even in the absence of cultural tools. We examined how task-naïve monkeys learn spatial and numerical concepts over time. Monkeys’ learning trajectories revealed successful learning of both numerical and geometric concepts. Discriminability effects showed that abstract quantitative features were stronger predictors of accuracy on both tasks than low-level visual similarity, reflecting abstract processing of both tasks. Cross-lagged analyses revealed that learning in the geometry task significantly predicted future gains in numerosity performance, even after controlling session-level trends, within-task stability, and general performance factors. Together, these findings provide evidence that spatial and numerical learning in primates rely on mutual cognitive processes. Such representations could form the evolutionary foundation for the well-documented “cognitive bridge” between numerical and spatial reasoning in human development.